Influence of multiple failure modes in reliability assessment of composite structures - Carlos Conceição António (2009)
The introduction of reliability assessment methods in the integrity analysis of composite laminates increased the complexity and the efficiency of the methodologies proposed in the literature. In this paper, approaches to obtain the reliability of whole composite laminate structures overcoming the expensive costs associated with exhaustive local reliability evaluation are proposed and analysed. The errors introduced by some approximations used in structural reliability calculation of composite laminate structures are studied within the context of robust design. The identification of different failure modes and its importance in reliability analysis are outlined and discussed.